Texnologik loyihalash – musiqa mashg’ulotlarida samarali ta’lim - Abdukarimova, E (SCIENCE and SOCIETY, 2019)
The article considers the advantages of organizing music lessons on the basis of technological designing on the topics of classical music in secondary schools. The author also describes the existing problems in training future music teachers at higher educational institutions.
Keywords: school; music culture; classic music; organization; technology; designing; future teacher; advantage